The Forecasting Inflation Movements in East Java Province Using the Auto-Regressive Integrated Moving Average (ARIMA) Approach - Budi Prasasti, Karari; Murdiyanto, Edi; Dwi Yulianti, Tiara; Aditama Putra Mukti Wibawa, Wahyu (BALANCE: Economic, Business, Management and Accounting Journal, 2025)
East Java is the province with the largest population in Indonesia. In addition, East Java's economic growth rate is the highest on the island of Java. The economic growth needs to be supported by other economic indicators. One of the most important macroeconomic indicators is inflation. This study discusses the inflation forecasting for East Java towards the end of 2024. Financial forecasting is crucial as it serves as the basis for government decision-making. The forecasting technique used in this study is ARIMA. The tests indicated that inflation in East Java will decrease towards the end of the year. In December, East Java will experience deflation of -1.75%. Meanwhile, in January and February 2025, the inflation rates were -2.07 and -2.39, respectively. Therefore, the East Java government must implement policies to anticipate this situation.